2004
DOI: 10.1161/01.atv.0000131265.76828.8a
|View full text |Cite
|
Sign up to set email alerts
|

DC Electric Fields Induce Distinct Preangiogenic Responses in Microvascular and Macrovascular Cells

Abstract: Objective-Electrical stimulation induces significant angiogenesis in vivo. We have shown recently that electrical stimulation induces directional migration, reorientation, and elongation of macrovascular endothelial cells. Because angiogenesis occurs mainly in the microvasculature, we have extended this observation to include human microvascular endothelial cells and compared the responses with that of vascular fibroblasts and smooth muscle cells and human umbilical vein endothelial cells. Methods and Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
111
3
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 39 publications
10
111
3
5
Order By: Relevance
“…The endothelial cells of the micro vessels seem to be sensitive to laser stimulation through the expression of gene proteins that regulate the cell cycle and the proliferation of these cells 27 . Bai et al 28 describe that electric fields of 150 to 400 mV/mm also perform migration, reorientation, and extension of the endothelial cells of micro-circulation vessels. The endothelial cells of micro-circulation present different behaviors when compared to macrovascular tissues, which suggests that each cellular type has a distinct disposition of receptors, and tolerance to different electric fields, contributing or not contributing to the activation of the vascular endothelial growth factor 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The endothelial cells of the micro vessels seem to be sensitive to laser stimulation through the expression of gene proteins that regulate the cell cycle and the proliferation of these cells 27 . Bai et al 28 describe that electric fields of 150 to 400 mV/mm also perform migration, reorientation, and extension of the endothelial cells of micro-circulation vessels. The endothelial cells of micro-circulation present different behaviors when compared to macrovascular tissues, which suggests that each cellular type has a distinct disposition of receptors, and tolerance to different electric fields, contributing or not contributing to the activation of the vascular endothelial growth factor 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Bai et al 28 describe that electric fields of 150 to 400 mV/mm also perform migration, reorientation, and extension of the endothelial cells of micro-circulation vessels. The endothelial cells of micro-circulation present different behaviors when compared to macrovascular tissues, which suggests that each cellular type has a distinct disposition of receptors, and tolerance to different electric fields, contributing or not contributing to the activation of the vascular endothelial growth factor 28 . Even with the positive action of laser and microcurrent upon the healing process in the various model types, such as skin 1 , diabetic ulcers 6 , and temperature burns 5,16,24 , their associated use still deserves more discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration and alignment: In vitro, electrical fields can induce directional migration and elongation of vascular cells and align the cells with their long axis perpendicular to electrical field vectors ( Bai et al 2004). Sato et al (2009) demonstrated that genes can control the direction of electrotaxis and field-strength-dependent direction of cell migration, i.e., the hormetic cell response to external direct current electrical fields.…”
Section: Atp and Ion Fluxmentioning
confidence: 99%
“…Here, I propose that the ATP gradients modulate export of H + by vacuolar H + -ATPase (V-ATPase) located on the surface of field cells and generate extracellular ion concentration gradients, ion currents and electrical fields along the paths of morphogen gradients. In vitro, electrical fields can induce directional migration and elongation of vascular cells and align the cells with their long axis perpendicular to electrical field vectors ( Bai et al 2004). I suggest that likewise, in vivo vascular transmural electrical fields induced by hormetic morphogen concentration gradients can modulate cell shape i.e.…”
mentioning
confidence: 99%